Formulation and Phytochemical Profile of a Product Prototype Infused with Cannabis sativa Leaves - Tongkasee, Pongsathorn; Srithat, Dutsdee; Sriyasak, Patcharawalai; Jitcharerntham, Anunkaorn; Piwgern, Teera; Khoontawad, Jarinya; Insuwan, Wilaiporn (Trends in Sciences, 2023)
This study investigated the formulation of a product prototype RMUTI-SKC by using the legal part of cannabis plants (leaves). Five product prototypes were composed of cannabis (leaves), stevia and mint. The herbs were added to improve the taste, smell and physical appearance properties of the product prototype which was yellowish-green. The analysis of the chemical properties found no heavy metals (Cd, As, and Pb) were observed (based on THAI community product standard, and demonstrated a moderate antioxidant activity, total phenolic content and total flavonoid content. The GC-MS profile of crude extracts analysis revealed the phytochemicals based on pharmacological action of essential oil, flavoring substance, anti-inflammatory, antioxidant, anti-bacterial, antidiabetic, antifungal and anti-cancer, respectively. The experimental results showed the pharmacological properties of the product prototype which can be a guideline for applying cannabis plants to other products. Further study on pathogen testing and product aging should be carried out to satisfy the quality of production. HIGHLIGHTS The formulation of a product prototype RMUTI-SKC by using the legal part of cannabis plants (leaves). The analysis of the chemical properties found no heavy metals (Cd, As and Pb) were observed (based on THAI community product standard, and demonstrated a moderate antioxidant activity, total phenolic content and total flavonoid content. GRAPHICAL ABSTRACT